Efficacy and safety of anti-CD38 monoclonal antibodies in patients with relapsed/refractory multiple myeloma: a systematic review and meta-analysis with trial sequential analysis of randomized controlled trials - Ye, Lu; Zhou, Fei; Cheng, Dongdong; Xie, Ming; Yan, Xiaoli; Xue, Yuyu; Yang, Qian; Jia, Rong; Zhong, Lili; Yang, Li; Zou, Liqun; Huang, Na (Frontiers in Oncology, 2023)
Objectives The current study aims to evaluate the safety and efficacy of anti-CD38 monoclonal antibodies (mAbs) among patients with relapsed/refractory multiple myeloma (RRMM) through meta-analysis. Methods As of June 2023, we searched PubMed, Web of Science, Embase and the Cochrane Library. Randomized controlled trials (RCTs) which compared the clinical outcomes of anti-CD38 mAbs plus immunomodulatory drugs (IMiDs) or proteasome inhibitors (PIs) plus dexamethasone and IMiDs (or PIs) and dexamethasone alone for RRMM patients were included. Efficacy outcomes were mainly evaluated with progression-free survival (PFS) and overall survival (OS). The safety was analyzed with hematologic and nonhematologic treatment-emergent adverse events (TEAEs). All results were pooled using hazard ratio (HR), relative risk (RR), and their 95% confidence interval (CI) and prediction interval (PI). Results This meta-analysis included 11 RCTs in total. Compared with IMiDs (or PIs) and dexamethasone alone, anti-CD38 mAbs in combination with IMiDs (or PIs) and dexamethasone significantly prolonged PFS (HR: 0.552, 95% CI = 0.461 to 0.659, 95% PI = 0.318 to 0.957) and OS (HR: 0.737, 95% CI = 0.657 to 0.827, 95% PI = 0.626 to 0.868) in patients with RRMM. Additionally, RRMM patients receiving anti-CD38 mAbs in combination with IMiDs (or PIs) and dexamethasone achieved higher rates of overall response (RR: 1.281, 95% CI = 1.144 to 1.434, 95% PI = 0.883 to 1.859), complete response or better (RR: 2.602, 95% CI = 1.977 to 3.424, 95% PI = 1.203 to 5.628), very good partial response (VGPR) or better (RR: 1.886, 95% CI = 1.532 to 2.322, 95% PI = 0.953 to 3.731), and minimum residual disease (MRD)-negative (RR: 4.147, 95% CI = 2.588 to 6.644, 95% PI = 1.056 to 16.283) than those receiving IMiDs (or PIs) and dexamethasone alone. For TEAEs, the rates of hematologic and nonhematologic TEAEs, including thrombocytopenia, neutropenia, upper respiratory tract infection (URTI), pneumonia, bronchitis, dyspnea, diarrhea, pyrexia, back pain, arthralgia, fatigue, insomnia, and hypertension, were higher in the anti-CD38 mAbs in combination with IMiDs (or PIs) and dexamethasone group than in the IMiDs (or PIs) and dexamethasone group. Conclusion Our study showed that anti-CD38 mAbs in combination with IMiDs (or PIs) and dexamethasone improved PFS and OS, and achieved higher rates of overall response, complete response or better, VGPR or better, and MRD-negative, as well as higher rates of thrombocytopenia, neutropenia, URTI, pneumonia, bronchitis, dyspnea, diarrhea, pyrexia, back pain, arthralgia, fatigue, insomnia, and hypertension in RRMM patients. Systematic review registration https://www.crd.york.ac.uk/PROSPERO/, identifier CRD42023431071.